The fundus changes in pathological myopia - Markosyan G.A.; Tarutta E.P; Tarasova N.A.; Maksimova M.V. (РМЖ "Клиническая офтальмология")
The article presents a literature review covering formation of views and the modern aspects of the etiology and pathogenesis of pathological myopia, which is one of the main causes of visual impairment and blindness worldwide. The article analyzes the data obtained on the basis of modern imaging technologies, such as optical coherence tomography, three-dimensional magnetic resonance imaging, which significantly deepened our understanding of an eye complications associated with high myopia. Nevertheless, information about the causes of the development of these lesions is clearly not enough, which makes it difficult to elaborate therapeutic measures to reduce or prevent the development of these complications. Despite recent advances in the treatment of choroidal neovascularization by administering drugs that block vascular endothelial growth factor and achievement of vitreoretinal surgery in vitreomacular traction syndrome, most of the complications of pathological myopia, such as macular atrophy, chorioretinal atrophy, and optic neuropathy, remain incurable.  A detailed analysis of the results of research by various authors showed that many factors affect the development of pathological myopia: biomechanical, biochemical, morphological, hemodynamic. These factors are key to the elaboration of methods for predicting and preventing the development of pathological myopia.  Keywords: pathological myopia, myopic maculopathy, posterior staphyloma, macular choroidal neovascularization.  For citation: Markosian G.A., Tarutta E.P., Tarasova N.A., Maximova M.V. The fundus changes in pathological myopia. Russian Journal of Clinical Ophthalmology. 2019;19(2):99–104.  About the authors: Gayane A. Markosian — MD, PhD, Leading Researcher of Department of Refractive Pathology, ORCID iD 0000-0002-2841-6396; Elena P. Tarutta — MD, PhD, Professor, Head of the Department of Refractive Pathology, ORCID iD 0000-0002-8864-4518; Natalia A. Tarasova — MD, PhD, Senior Researcher of the Department of Refractive Pathology, ORCID iD 0000-0002-3164-4306;  Marina V. Maksimova — Researcher of the Department of Refractive Pathology, ORCID iD 0000-0002-3749-3668. Moscow Helmholtz Research Institute of Eye Diseases. 14/19, Sadovaya-Chernograyazskaya str., Moscow, 105062, Russian Federation. Contact information: Natalia A. Tarasova, e-mail: tar221@yandex.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 14.11.2018.